Adjusting to Indonesia’s Culture: The Case of Expatriates in the Education Industry - Mirwan Surya Perdhana; Dian Sawitri; Reiner Abeltua Siregar (Universitas Ahmad Dahlan, 2019)
AbstractÂ Globalization has resulted in an increased number of foreign workers in Indonesia. Nevertheless, not all foreign workers can easily adapt to the culture, business, and social situation of the host country. According to cross-cultural literature, the cultural adjustment has been considered as the prerequisite for the success of the expatriates overseas. This study aims to investigate factors that affect the success of the international assignment. Using a qualitative case study approach, this study interviewed five expatriates working in the education industry in Central Java based on the U-curve cultural adjustment theory. The result of this study demonstrates that the inability of an expatriate to adjust with the host country was due to the lack of preparation toward the culture of the host country, resistance with the new culture, conflict-avoiding behavior, and the lack of two-way communication between the expatriate and the local staffs.Keywords: Cross-cultural adjustment, cross-cultural management, expatriate, international assignment, U-curve.